ANALISIS KEMAMPUAN HIGHER ORDER THINKING SKILL (HOTS) SISWA DALAM DISKUSI KELOMPOK PADA MATA PELAJARAN PPKN DI SMP NEGERI 22 KOTA JAMBI - Nabila Rosalia Putri; Firman; Alif Aditya Candra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Group discussion is a communication method involving two or more individuals aimed at exchanging ideas, finding solutions, and deepening understanding of a particular topic. This research was motivated by the lack of students' Higher Order Thinking Skills (HOTS) during group discussion activities. The study aims to identify the HOTS demonstrated by students in group discussions in Civic Education (PPKn) classes and to examine the role of PPKn teachers in facilitating the development of students' HOTS during the discussion process. This study employed a qualitative approach with a phenomenological research design. The research data were collected through observation, interviews, and documentation. Interviews were conducted with students, teachers, and the vice principal for student affairs. The findings revealed that not all students were able to demonstrate HOTS during group discussions. However, among the HOTS aspects of analyzing, evaluating, and creating, the analyzing aspect was the most dominant skill demonstrated by students. Students were able to analyze information and issues discussed, express opinions based on logical reasoning, and formulate ideas and solutions to the problems presented. Although not all students were capable of generating new and innovative ideas, group discussion activities can serve as an effective medium for developing students' Higher Order Thinking Skills.